2012
DOI: 10.1063/1.4746254
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Schottky barrier height between Ni-InGaAs alloy and In0.53Ga0.47As

Abstract: Articles you may be interested inVery low resistance alloyed Ni-based ohmic contacts to InP-capped and uncapped n+-In0.53 Ga0.47As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In our previous work, 8 we observed that the qualities that lay in the NiInGaAs layer have as a contact. In order to understand the factors that lead to the creation of these qualities, additional material characterization techniques were used.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In our previous work, 8 we observed that the qualities that lay in the NiInGaAs layer have as a contact. In order to understand the factors that lead to the creation of these qualities, additional material characterization techniques were used.…”
Section: Introductionmentioning
confidence: 82%
“…[4][5][6][7] We have recently investigated this system electrically and showed a near ideal current-voltage behavior with a Schottky barrier height of 0.24 6 0.01 eV. 8 In x Ga 1Àx As based transistors with NiInGaAs S/D regions were investigated and found to function successfully with a very high peak velocity. 6,9 Recently, we 8 as well as others 10 analyzed the NiInGaAs phase formed at the interface between Ni and InGaAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the NiInGaAs comes now in direct contact with undoped InGaAs. Rather than an ohmic contact, this could result in a Schottky barrier [32]. In this instance, R on should show a negative temperature dependence, as observed in Fig.…”
Section: The Role Of the Top Contactmentioning
confidence: 91%
“…According to thermionic emission theory, the Schottky diode's current-voltage characteristics are already expressed in the literature [10][11][12][13][14]. One can find the I-V graph for different metal types in [10][11][12][13][14]. In the case of forward bias current for nonideal conditions, the equation is expressed as follows:…”
Section: Ideality Factormentioning
confidence: 99%